Expression and prognostic relevance of the death receptor CD95 (Fas/APO1) in renal cell carcinomas - Macher-Göppinger, Stephan; Lorenzo Bermejo, Justo; Wagener, Nina; Hohenfellner, Markus; Haferkamp, Axel; Schirmacher, Peter; Roth, Wilfried (Cancer letters, 2011)
CD95 (Fas/APO1) is one of the best known members of the death receptor family which can either mediate apoptosis or activate tumor-promoting pathways. Using a tissue microarray we investigated the association between the expression of CD95 and prognosis in 617 patients with renal cell carcinomas (RCCs). CD95 was expressed in the vast majority of RCCs. High CD95 expression was associated with lymph node metastasis and correlated negatively with disease-specific survival. Multivariate Cox regression analysis confirmed CD95 expression as an independent prognostic factor. In conclusion, high CD95 expression is a negative independent prognostic factor in RCCs which could be used to identify high-risk patients with a poor clinical prognosis.